2021
DOI: 10.1038/s41467-021-27194-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated discovery of superoxide-dismutase nanozymes via high-throughput computational screening

Abstract: The activity of nanomaterials (NMs) in catalytically scavenging superoxide anions mimics that of superoxide dismutase (SOD). Although dozens of NMs have been demonstrated to possess such activity, the underlying principles are unclear, hindering the discovery of NMs as the novel SOD mimics. In this work, we use density functional theory calculations to study the thermodynamics and kinetics of the catalytic processes, and we develop two principles, namely, an energy level principle and an adsorption energy prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 73 publications
0
69
0
Order By: Relevance
“…[169][170][171] Additionally, the intrinsic POD activity was detected in several other monometallic oxides, including TiO 2 , 172 NiO, 173 Cu 2 O, 174 ZrO 2 , 175 RuO 2 , 176 and four perovskites (LaNiO 3 , 177 LaCoO 3 178 LaMnO 3 , 179 and SrFeO 3 179) as well as the ''noble metal nanoparticles'', e.g., Au, 180 Ag, 181 Pt, 182 Pd, 183 Ir, 184 and Ru. 185 Using density functional theory calculations, the mechanisms of nanozyme studies indicated that the energy transfer in catalytic processing related to hydrogen peroxide is directly related to the architecture of the nanomaterials, including POD-like activities, 113,186,187 CAT-like activities, 119,186 SOD-like activities, 186,188,189 and OXD-like activities. 120,186,189 Their oxidoreductase-like activity originates from their unique architectures in these inorganic nanomaterials, such as the characteristic metal architectures in the protein for their specific catalytic behaviours (Fig.…”
Section: Xiao-lan Huangmentioning
confidence: 99%
“…[169][170][171] Additionally, the intrinsic POD activity was detected in several other monometallic oxides, including TiO 2 , 172 NiO, 173 Cu 2 O, 174 ZrO 2 , 175 RuO 2 , 176 and four perovskites (LaNiO 3 , 177 LaCoO 3 178 LaMnO 3 , 179 and SrFeO 3 179) as well as the ''noble metal nanoparticles'', e.g., Au, 180 Ag, 181 Pt, 182 Pd, 183 Ir, 184 and Ru. 185 Using density functional theory calculations, the mechanisms of nanozyme studies indicated that the energy transfer in catalytic processing related to hydrogen peroxide is directly related to the architecture of the nanomaterials, including POD-like activities, 113,186,187 CAT-like activities, 119,186 SOD-like activities, 186,188,189 and OXD-like activities. 120,186,189 Their oxidoreductase-like activity originates from their unique architectures in these inorganic nanomaterials, such as the characteristic metal architectures in the protein for their specific catalytic behaviours (Fig.…”
Section: Xiao-lan Huangmentioning
confidence: 99%
“…OVs and free radicals generated by interfacial catalysis play an important role. 55,56 The free radicals are produced by the interaction between CeO 2 and substrate and the cycling of Ce 4+ /Ce 3+ , which plays a crucial role commonly including hydroxyl radical (•OH) and superoxide radical (•O 2…”
Section: Catalytic Mechanism Of Ceo 2 Nmsmentioning
confidence: 99%
“…Density functional theory (DFT) has been used to explore the mechanisms and kinetics of enzyme-mimetic nanomaterials in previous studies. For SOD-like activities, two-step mechanism was verified during the procession of scavenging O 2 • – : the catalyst first accepts an electron from O 2 • – , and then transfer the electron to another O 2 • – in the presence of protons in the solution . Therefore, we performed a DFT calculation to further analyze the reactivity of MOF-818 with intact structure, or its counterpart wherein Zr SBU was removed, respectively.…”
mentioning
confidence: 99%
“…• − in the presence of protons in the solution. 45 Therefore, we performed a DFT calculation to further analyze the reactivity of MOF-818 with intact structure, or its counterpart wherein Zr SBU was removed, respectively. As illustrated in Figure 3f, the HOMO− LUMO gap of MOF-818 was 0.13 eV, while the barrier increased to 0.35 eV after the removal of Zr SBU.…”
mentioning
confidence: 99%